P13.11 Transcriptional CDK inhibitors, CYC065 and THZ1 promote apoptosis in preclinical models of primary and recurrent GBM tumour cells and glioma stem cells. (9th September 2021) - Juric, V; Duessmann, H; Jahns, H; Verreault, M; Idbaih, A; Lamfers, M L; Hopkins, A M; Prehn, J H; Rehm, M; Murphy, B M
Abstract: BACKGROUND: Activation of cyclin-dependent kinases (CDKs) contributes to the uncontrolled proliferation of tumour cells. Genomic alterations that lead to the constitutive activation of CDKs are a feature of many tumours including glioblastoma (GBM), the most common and aggressive primary brain tumour. Patient resistance to the current standard of care, temozolomide and radiotherapy, is common and highlights the need to discover more effective treatment strategies. Additionally, glioma stem cells (GSCs), tumour initiating cells contribute to treatment resistance in GBM. Targeting GBM tumour cells and GSCs using transcriptional CDK inhibitors, CYC065 and THZ1 is a potential novel treatment to prevent relapse of the tumour. MATERIAL AND METHODS: The therapeutic efficacy of two CDK inhibitors (CKIs) was tested in a panel of ten low-passage GBM patient-derived gliomasphere cultures and semi-in vivo chick embryo xenograft models. Specifically, transcriptional inhibitors targeting CDK9/2 (CYC065) and CDK7 (THZ1) were used. Mechanism of cell death was examined following CKI treatment. Additionally, dependence on anti-apoptotic proteins was studied using genetic depletion and BH3 profiling. Fluorescence activated cell sorting (FACS) and light-sheet fluorescence microscopy (LSFM) were employed to study stem cell populations in recurrent GBM and evaluation of CKI efficacy against GSCs. RESULTS: We here demonstrate that CYC065 and THZ1 treatments cause loss of cell viability and induce caspase-dependent apoptosis in primary and recurrent patient-derived gliomaspheres while sparing primary cortical neurons. Importantly, apoptosis responses manifested across a range of time points that significantly correlated with the cell doubling time. Mechanistically, CYC065 and THZ1 downregulate the anti-apoptotic protein Mcl-1, which suffices to sensitise gliomasphere cultures to treatment-induced apoptosis in a Bim-dependent manner. Additionally, high expression levels of chemo- and radio-resistant GSCs were found in recurrent gliomaspheres. CKIs induced apoptosis in isolated CD133 and CD44 biomarker-positive cells while TMZ was ineffective, highlighting the potential of these drugs to overcome resistance to conventional chemotherapy. Additionally, using LSFM we shown that CD133, CD44 GSC biomarker-negative cells convert into GSC biomarker-positive cells and contribute to the enrichment in GSCs in recurrent GBM which could potentially explain the TMZ ineffectiveness. Finally, CKIs reduced proliferation and promoted apoptosis in chick embryo xenograft models of primary and recurrent GBM. CONCLUSION: Collectively, these data demonstrate that CYC065 and THZ1 display high anti-cancer activity in primary and recurrent GBM and provide scientific rationale for the further development of CDK inhibitors to potentiate their clinical utilization in the future.